Pré-seleção de fornecedores no contexto de negócios e Indústria 4.0 utilizando MCDA - Spinardi, Maurício (Universidade Federal de São Carlos, 2019)
With the current trend of modernisation, automation and data exchange, also known as Industry 4.0, the number of new actors in the corporate environment has grown, along with the need for tools to streamline industrial processes. Computing platforms, such as e-marketplaces, seek to respond to this demand by providing resources to facilitate the initial connection and relationship between clients and suppliers. However, business-tobusiness e-marketplaces still have a number of limitations, such as the high specificity inherent in the supplier selection problem. Considering this problem and context, this study proposes a new approach to supplier selection in e-marketplaces. In this approach, the problem is divided into two stages: pre-selection, carried out by the e-marketplace, and final decision, carried out by the client. Functioning as a filtering process, the aim of pre-selection is to construct a short, pre-processed list of alternatives for the second step – the final decision – to simplify and streamline the client’s analysis. To verify the utility and feasibility of pre-selection, a methodology structured around four main steps was proposed: (1) defining a multi-criteria decision analysis technique, (2) defining pre-selection criteria, (3) validating and defining the respective weights for the pre-selection criteria and (4) defining a proposal for rejecting suppliers. Consequently, this approach streamlines the efficiency of the selection process and improves the maintainability of e-marketplaces.
Supplier pre-selection in e-marketplaces for Industry 4.0 using MCDA techniques
Keywords: Automação industrial; Cadeia de suprimentos; Computadores na indústria; Industrial automation; Supply chain; Computers in industry; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO; ENGENHARIAS::ENGENHARIA DE PRODUCAO